Osphranter rufus (Diprotodontia: Macropodidae). (23rd December 2020) - Freedman, Calli R; Rothschild, Daniel; Groves, Colin; Newman, Amy E M
Abstract: Osphranter rufus (Desmarest, 1822) is a macropod commonly called the red kangaroo and is the largest extant marsupial. Sexually dimorphic in size and coat color, this large macropod is one of four species in the genus Osphranter . In general, males are larger than females, and are reddish-brown in color, whereas females are bluish-gray. O. rufus is endemic to Australia, where it inhabits both arid and semiarid areas with wide habitat preferences that include open plains, open desert, grassland, woodland, or shrubland habitats. Although it is regularly harvested for its meat and hide, O. rufus is an abundant species that is not of special conservation concern and it is listed as "Least Concern" by the International Union for Conservation of Nature and Natural Resources.